The Elias University Hospital Approach: A Visual Guide to Ultrasound-Guided Botulinum Toxin Injection in Spasticity: Part II—Proximal Upper Limb Muscles - Popescu, Marius Nicolae; Căpeț, Claudiu; Beiu, Cristina; Berteanu, Mihai (Toxins, 2025)
Ultrasound-guided botulinum toxin type A (BoNT-A) injections play a critical role in the management of upper limb spasticity. This is the second part of ‘The Elias University Hospital Approach: A Visual Guide to Ultrasound-Guided Botulinum Toxin Injection in Spasticity’ and it focuses on the proximal upper limb muscles, complementing the first part, which addressed the distal upper limb muscles. This guide provides a detailed analysis of ultrasound anatomy, clinical relevance, and injection strategies for the latissimus dorsi, teres major, subscapularis, pectoralis major, pectoralis minor, deltoid, triceps brachii, biceps brachii, brachialis, and brachioradialis. Using the Elias University Hospital (EUH) model, it presents a structured approach to BoNT-A administration, ensuring precision, safety, and optimal outcomes in spasticity management. To enhance clinical application, this guide incorporates a wide array of high-quality ultrasound images and dynamic videos, offering a comprehensive and practical understanding of scanning techniques, anatomical structures, and injection procedures. This second part of the series serves as an essential reference for clinicians, aligning with the first installment to provide a complete and systematic approach to ultrasound-guided BoNT-A therapy for upper limb spasticity.